2017
DOI: 10.1021/acs.jproteome.7b00133
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Association of Salivary Proteins with Age, Sex, Body Mass Index, Smoking, and Education

Abstract: Whole saliva is gaining more and more attention as a diagnostic tool to study disease-specific changes in human subjects. Prior to the actual disease-related analyses, it is important to understand the influence of various demographic variables and coupled phenotypes on salivary protein signatures. In a cross-sectional approach, we analyzed the influence of age, sex, body mass index (BMI), smoking, and education on salivary protein signatures in whole saliva samples of 187 individuals. Subjects were randomly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 58 publications
0
13
0
1
Order By: Relevance
“…In a recent population‐based approach, Murr et al. used LC‐MS/MS to examine the variation of salivary protein levels in 187 normal individuals and test the correlation of protein levels with age, sex, body mass index (BMI), smoking, and education . They demonstrated that smoking status (54 proteins) and age (12 proteins) were associated with salivary protein abundance and composition among 304 confidentially identified proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent population‐based approach, Murr et al. used LC‐MS/MS to examine the variation of salivary protein levels in 187 normal individuals and test the correlation of protein levels with age, sex, body mass index (BMI), smoking, and education . They demonstrated that smoking status (54 proteins) and age (12 proteins) were associated with salivary protein abundance and composition among 304 confidentially identified proteins.…”
Section: Discussionmentioning
confidence: 99%
“…We used the Human Salivary Proteome Wiki (https://salivaryproteome.nidcr.nih.gov/) to obtain proteome data for the whole saliva, ductal saliva from the PAR, SM, and SL, as well as from blood plasma. The database provides mass-spectrometry-based abundance data for approximately 3,000 proteins compiled from multiple studies (Murr et al, 2017), including those that focused on ductal secretions (Denny et al, 2008). Similar to the comparison approach that we used for integrating GTEx data, we used log transformation (log 10 (1+normalized abundance)) for each dataset.…”
Section: Identifying Genes With Salivary Gland Specific Expressionmentioning
confidence: 99%
“…We used the Human Salivary Proteome Wiki ( https://salivaryproteome.nidcr.nih.gov/ ) to obtain proteome data for whole saliva, ductal saliva from the PAR, SM, and SL, as well as from blood plasma. The database provides mass-spectrometry-based abundance data for approximately 3,000 proteins compiled from multiple studies (Murr et al, 2017) , including those that focused on ductal secretions (Denny et al, 2008) . Similar to the comparison approach that we used for integrating GTEx data, we used log transformation (log 10 (1+normalized abundance)) for each dataset.…”
Section: Data Analysis and Integration Of Datasetsmentioning
confidence: 99%